Non functionant adrenocortical carcinoma: a diagnostic problem. - Vallverdú, Martín; Sanguinetti, Julio; Torres, Marcos; Bianchi, Carlos; Silva, Julio (Cirugía del Uruguay, 1987)
Two cases of non functionant adrenocortical carcinoma are presented. Preoperatory and also intraoperatory diagnostic difficultles are pointed out. Study protocol is discussed and the high value of CAT sean is signalized.